Anatoliy Feodosiyovych Levytskiy - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article is devoted to the 60th anniversary of the Head of the Department of Pediatric Surgery of the National Medical University, Doctor of Medicine, Professor Levitsky A. F.